Analysis of Students' Mathematical Communication Ability on Two Variable Linear Equation Systems (SPLDV) Materials - Ismiatin Nisa; Slamet Soro (Universitas Negeri Makassar, 2021)
This study aims to determine and analyze aspects of students' mathematical communication skills in the material of two-variable linear equations (SPLDV. The study was conducted with a sample of 5 students from 30 populations with different abilities and were taken randomly at one junior high school in Jakarta. used is descriptive qualitative. The research instrument is a test of mathematical communication skills in the form of 5 essay questions and interviews. The results of the tests that have been carried out show the results of communication skills in the medium category because there are 3 questions whose percentage is in the medium category and 2 other questions in the low category It can be seen from the percentage of scores per item, that is question no. 1 has a percentage of 60%. Question no.2 has a percentage of 45%. Question no.3 has a percentage of 40%. Question no.4 has a percentage of 30%. And questions no.5 with the acquisition of a percentage of 25%. Thus, it can be concluded that the ability to communicate The mathematical students on the material of a system of linear equations of two variables are included in the medium category.